Drug fever induced by antibiotics of β-lactams in a patient after posterior cervical spine surgery—A case report and literature review - Hu, Yunxiang; Han, Jun; Gao, Lin; Liu, Sanmao; Wang, Hong (Frontiers in Surgery, 2023)
Drug fever is a febrile reaction that temporarily emerges with the administration of a drug or a variety of drugs and disappears after cessation of the targeting agent. There are few previous reports about drug fever but are mainly to patients accompanied with no surgical intervention. Based on literature reviewed, drug fever in patient after posterior cervical spine surgery has never been mentioned before, therefore, we present a 56-year-old man diagnosed with drug fever after posterior cervical spine surgery for traumatic cervical myelopathy. Fortunately, his body temperature rapidly came down in two days after discontinuing the antibiotics, he was discharged after two more days of observation, patient recovered well without any further complaints. Early diagnosis of drug fever may greatly reduce inappropriate and potentially detrimental diagnostic and therapeutic interventions. To patients with persistent fever, if it happened days after surgery, particularly when it is without any infectious evidence, then it is necessarily important to consider a possible reason of drug-induced fever.